Words against bourgeois sensibility?: Lexicometric analysis of 20th Century Art Manifestos - Luna, Diego (Escritura e Imagen, 2024)
The critical analysis of verbal discourses constitutes a useful strategy for understanding the way art manifestos attempt to challenge certain narratives, inaugurate alternative realities, and construct their own identity. The present study stemmed from the need to further delve into the knowledge of 20th-century artistic manifestos, assuming as its main objective the exploration of the evolution of the political potential of art in modern and postmodern manifestos from a lexicometric approach. The results obtained reveal a progressive depoliticization of the artistic discourses gathered in these writings: while, on the one hand, modern manifestos devote great efforts to attacking bourgeois sensibility and all it represents, on the other hand, postmodern texts completely forget the anti-ourgeois objectives and seem to focus on reflecting upon an already consolidated system, the art system, without threatening its existence at any point.